Solubilization of Single-walled Carbon Nanotubes with Single-stranded DNA Generated from Asymmetric PCR - Liang, Zhiqiang (Molecular Diversity Preservation International (MDPI), 2007)
Carbon nanotubes (CNTs) can be effectively dispersed and functionalized by wrapping with long single-stranded DNA (ssDNA) synthesized by asymmetric PCR. The ssDNA-CNTs attached on surface of glass carbon electrode made it possible for electrochemical analysis and sensing, which was demonstrated by reduction of H(2)O(2) on hemoglobin/ssDNA-CNTs modified electrodes. This research showed the potential application of DNA-functionalised CNTs in construction of future electrochemical biosensors.